2012
DOI: 10.1158/1078-0432.ccr-12-1967
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and Sorafenib Metabolism

Abstract: Purpose To investigate the role of ontogeny in sorafenib metabolism to the equipotent active metabolite sorafenib N-oxide. Experimental Design Steady-state pharmacokinetic studies of sorafenib and metabolites were performed in thirty children and young adults (17 males; median age, 9.5 years) receiving sorafenib 150 mg/m2 or 200 mg/m2 twice daily. Sorafenib metabolism was evaluated in vitro at 10 µM using a panel of purified human cytochrome P450 (CYP) enzymes. Sorafenib metabolism and CYP3A4 expression was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…In addition, we used commercial pooled human microsomes (CHLMs) as a control. In CHLMs, the K m value was 11.48±4.19 µM for oxidation and 2.89±0.29 µM for glucuronidation, which was equal to that reported in the previous publication (12.1±0.71 µM and 3.6±0.22 µM, respectively) [33]. Furthermore, we have measured the UGT1A9 protein content by UPLC-MS/MS.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, we used commercial pooled human microsomes (CHLMs) as a control. In CHLMs, the K m value was 11.48±4.19 µM for oxidation and 2.89±0.29 µM for glucuronidation, which was equal to that reported in the previous publication (12.1±0.71 µM and 3.6±0.22 µM, respectively) [33]. Furthermore, we have measured the UGT1A9 protein content by UPLC-MS/MS.…”
Section: Discussionsupporting
confidence: 81%
“…First, sorafenib concentrations can be variable in patients receiving this medication, possibly due to age, gender, and effects of concomitant medications (chemotherapy or CYP3A4 inhibitors) on the metabolism of the drug. 25,26,48 Variability in FLT3 inhibition as assessed by the PIA assay has previously been noted with sorafenib. 26 Second, some The Inhibited group consisted of 14 patients whose P-FLT3 levels were ,15% of baseline at $1 point during the first cycle of therapy.…”
Section: Org Frommentioning
confidence: 79%
“…3C). Ex vivo metabolism studies indicated that, compared to mice and humans (9), rat liver microsomes lack a significant capacity to form SG (Fig. 3D).…”
Section: Resultsmentioning
confidence: 99%
“…ATP-dependent transport of sorafenib and SG was determined by subtracting AMP-dependent transport from ATP-dependent transport, with both expressed in pmol/min/mg, after normalization for non-specific transport observed in control vesicles. Uptake experiments were carried out at a concentration of 10 µM, which is equivalent to average sorafenib plasma steady-state concentrations achievable in adults and children treated at 400 mg or 200 mg/m 2 twice daily (9, 21). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation